2021
DOI: 10.1371/journal.pone.0251776
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spatial association of geographical detector-based landslides and environmental factors in the southeastern Tibetan Plateau, China

Abstract: Steep canyons surrounded by high mountains resulting from large-scale landslides characterize the study area located in the southeastern part of the Tibetan Plateau. A total of 1766 large landslides were identified based on integrated remote sensing interpretations utilizing multisource satellite images and topographic data that were dominated by 3 major regional categories, namely, rockslides, rock falls, and flow-like landslides. The geographical detector method was applied to quantitatively unveil the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…By analyzing the spatio-temporal evolution characteristics of new urbanization in central China, it is found that the spatial dependence and heterogeneity of new urbanization are not significant, and it is difficult to accurately identify its driving factors by traditional statistical methods. As an effective tool to identify spatial heterogeneity features, geographic detectors can better analyze the causality generated by spatial correlation, diagnose and solve spatial heterogeneity and its causes [ 46 ]. This paper mainly uses factor detector and interaction detector to explore the influence degree of each driving factor on new urbanization in central China and the influence degree of each factor interaction.…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing the spatio-temporal evolution characteristics of new urbanization in central China, it is found that the spatial dependence and heterogeneity of new urbanization are not significant, and it is difficult to accurately identify its driving factors by traditional statistical methods. As an effective tool to identify spatial heterogeneity features, geographic detectors can better analyze the causality generated by spatial correlation, diagnose and solve spatial heterogeneity and its causes [ 46 ]. This paper mainly uses factor detector and interaction detector to explore the influence degree of each driving factor on new urbanization in central China and the influence degree of each factor interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of any assumption, the geographic detector is a tool for identifying the links between elements affecting spatial differentiation and geographical phenomena [76]. Multivariable collinearity does not alter the computation or the outcome.…”
Section: Geographic Detectormentioning
confidence: 99%
“…Even though the combination is optional, spatial discretization covers almost all available choices where break numbers can be integer sequences depending on observations and practical requirements. A parameter combination with the highest PD is the best choice of a continuous variable for spatial discretization as it presents the variable's highest importance in stratified spatial heterogeneity [92,93].…”
Section: Factor Detectormentioning
confidence: 99%